Exploring Russian tap-code text entry adaptions for users with reduced target hitting accuracy - Sandnes, Frode Eika; Medola, Fausto Orsi [UNESP] (Association for Computing Machinery (ACM), 2016)
Text is still the dominant form of human-computer-human communication. Users with certain motor or visual impairments may be unable to use certain text entry interfaces such as the small virtual keyboards on mobile phones effectively due to challenges hitting small targets. Despite the vast amount of research into text entry, no efforts have explored the so-called Russian tap-codes, or knock codes, which were commonly used to communicate between prison inmates. Tapping does not require the user to hit a specific target. This study proposes a theoretical framework for classifying text entry designs. The framework is used to explore 16 text entry designs, namely the classic Russian tap code and design variations exploiting more recent results in text entry research and the context of current hardware, allowing unfeasible designs to be easily eliminated.
Keywords: Accessibility; Low-vision; Motor impairment; Target hitting; Text entry